Effect of iron and zinc supplementation in the treatment of malaria in children - Danny Dasraf; Bugis Mardina Lubis; Bidasari Lubis; Nelly Rosdiana; Munar Lubis; Syahril Pasaribu (Indonesian Pediatric Society Publishing House, 2016)
Background Iron and zinc administration for children with malaria in endemic area were known to decrease parasitemia but data on their effectiveness when given together to increase reticulocytes as erythropoiesis parameter and hemoglobin is insufficient. Objective To determine the effect of zinc to increase iron absorption in the treatment of Plasmodium falciparum malaria in children. Methods Children with positive Plasmodium falciparum on their blood smear (n=86) examination were randomly assigned to daily supplementation of iron 6 mg per kg body weight per day plus placebo or iron plus zinc 10 mg per day for 30 days. Venous blood specimens were collected at the start and at the end of the study. Results Sixty-nine children completed the supplementations and had both baseline and follow-up blood specimen study. After 30- day supplementation, the iron plus placebo and iron plus zinc groups showed significant difference on hemoglobin concentration (0.58 and 0.09 g/dl; P<0.05). There was no significant difference in reticulocyte production index and reticulocyte count before and after intervention in both groups. There was only significant difference in red blood cells concentration after supplementation of iron plus placebo and iron plus zinc (4.7 in 4.5 million/μl; P<0.05). Conclusions Iron supplementation with or without zinc shows significant increase of hemoglobin concentration. It is slightly higher in iron plus placebo group.